Career paths in psychology where your degree can take you - Sternberg, Robert J. (American Psychological Association, 2017)
"The chapters describe 30 different graduate-level careers for those holding a PhD, EdD, or PsyD in three distinct areas of endeavor: academia, clinical and counseling psychology specialized settings such as for-profit businesses, nonprofits, the military, and schools. Each chapter explores a different career, including typical daily activities, the approximate range of compensation, advantages and disadvantages of the career, opportunities for employment and advancement, and how to plan one's educational and professional experiences to prepare for this specialty."--Provided by publisher.